THE INFORMATIVE VALUE OF THE ASSESSMENT SCALES IN THE CHANGE BLOOD BIOMARKERS OF PATIENTS WITH ISCHEMIC STROKE - Gazieva Sh. R. (Modern American Journals, 2025)
For a quick assessment of the condition and the development of an individual treatment plan in patients with ischemic stroke, the scale indicators correlate with more pronounced neurological symptoms, an aggravation of the course of the disease and an increase in the duration of hospitalization. For the rapid assessment of neurological status and the development of individualized therapy, the use of the Rankin, Rivermead, MoSs, and NIHSS scales is recommended. Studies have also established the effectiveness of correcting the standard therapy for ischemic stroke by including the nootropic oxiracetam, the dietary supplement GLA, the restoring deficiency of DGLA and the anticoagulant rivaroxaban, which significantly reduce the duration and unfavorable outcomes of rehabilitation compared with conventional therapy.
Keywords: Ischemic stroke, Rankin, Rivermead, MoSa, NIHSS, PLA2G2E, DGLA and PADI4, D-dimer.